2020
DOI: 10.3389/fphar.2020.601325
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Senescence in Kidney Fibrosis: Pathologic Significance and Therapeutic Strategies

Abstract: Age-related disorders such as chronic kidney disease (CKD) are increasingly prevalent globally and pose unprecedented challenges. In many aspects, CKD can be viewed as a state of accelerated and premature aging. Aging kidney and CKD share many common characteristic features with increased cellular senescence, a conserved program characterized by an irreversible cell cycle arrest with altered transcriptome and secretome. While developmental senescence and acute senescence may positively contribute to the fine-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 181 publications
1
44
0
1
Order By: Relevance
“…It is reported that proximal tubular cells arrested in the G2/M phase after an injury are responsible for the fibrotic response, which leads to CKD [83,84,86]. Hence, helping cells abrogate the G2/M arrest and preventing profibrotic growth factor release are new strategies for avoiding renal fibrosis [81,87]. According to our results, several pathways related to the cell cycle may be covered by CHM clusters, especially in pathways related to G2/M checkpoints.…”
Section: Principal Findingssupporting
confidence: 58%
See 1 more Smart Citation
“…It is reported that proximal tubular cells arrested in the G2/M phase after an injury are responsible for the fibrotic response, which leads to CKD [83,84,86]. Hence, helping cells abrogate the G2/M arrest and preventing profibrotic growth factor release are new strategies for avoiding renal fibrosis [81,87]. According to our results, several pathways related to the cell cycle may be covered by CHM clusters, especially in pathways related to G2/M checkpoints.…”
Section: Principal Findingssupporting
confidence: 58%
“…A previous study found that specific CHMs are involved in DKD-related modulation of microRNA [79]. Besides, the importance of cell cycle arrest in treating CKD seems to be increasing in recent years [80][81][82][83][84]. Cell division involves the following four phases: G0-G1, S, G2, and M. To repair the injured tissue ultimately, DNA is replicated and divided in the process of the cell cycle.…”
Section: Principal Findingsmentioning
confidence: 99%
“…2 These cellular and molecular systems bear several similarities to pathways that are modified by programming such as decreased apoptosis and proteasome function 3 and fibrosis. 4 Thus, it is not surprising their interactions occur between developmental programming and ageing as will be described here. In this review, we will first address some of the fundamental principles of programming and ageing interactions.…”
Section: Introductionmentioning
confidence: 73%
“…Another review considers the seven pillars of ageing as metabolism, macromolecular damage, epigenetics inflammation, stem cells and regeneration, proteostasis and adaptation to stress 2 . These cellular and molecular systems bear several similarities to pathways that are modified by programming such as decreased apoptosis and proteasome function 3 and fibrosis 4 . Thus, it is not surprising their interactions occur between developmental programming and ageing as will be described here.…”
Section: Introductionmentioning
confidence: 99%
“…SASP has been linked to mTOR activation (Herranz et al, 2015). SASP involves the secretion of pro-fibrotic factors that promote kidney fibrosis (Xu et al, 2020). Wnt9-TGFÎČ1 pathway has been shown to be involved in this process (Luo et al, 2018).…”
Section: Chloride Channel Accessory 1 Overexpression Promotes Saspmentioning
confidence: 99%